Continent catheterizable tubes/stomas in adult neuro‐urological patients: A systematic review. Issue 7 (31st January 2017) - Phé, Véronique; Boissier, Romain; Blok, Bertil F. M.; Del Popolo, Giulio; Musco, Stefania; Castro‐Diaz, David; Padilla Fernández, Bárbara; Groen, Jan; Hamid, Rizwan; 't Hoen, Lisette; Ecclestone, Hazel; Kessler, Thomas M.; et al.
Abstract : Aims: To systematically review all available evidence on the effectiveness and complications of continent cutaneous stoma or tube (CCS/T) to treat bladder‐emptying difficulties in adult neuro‐urological patients. Methods: The search strategy and studies selection were performed on Medline, Embase, and Cochrane using the PICOS method according to the PRISMA statement (CRD42015019212;http://www.crd.york.ac.uk/PROSPERO ). Results: After screening 3, 634 abstracts, 11 studies (all retrospective, enrolling 213 patients) were included in a narrative synthesis. Mean follow‐up ranged from 21.6 months to 8.7 years (median: 36 months, IQR 28.5‐44). At last follow‐up, the ability to catheterize rate was ≥84% (except in one study: 58.3%) and the continence rate at stoma was >75%. Data comparing health‐related quality‐of‐life before and after surgery were not available in any study. Overall, 85/213 postoperative events required reoperation: 7 events (7 patients) occurring ≤3 months postoperatively, 22 events (16 patients) >3 months, and 56 events (55 patients) for which the time after surgery was not specified. Sixty additional complications (60 patients) were reported but did not require surgical treatment. Tube stenosis occurred in 4‐32% of the cases (median: 14%, IQR 9‐24). Complications related to concomitant procedures (augmentation cystoplasty, pouch) included neovesicocutaneous fistulae, bladder stones, and bladder perforations. Risk of bias and confounding was high in all studies. Conclusions: CCS/T appears to be an effective treatment option in adult neuro‐urological patients unable to perform intermittent self‐catheterization through the urethra. However, the complication rate is meaningful and the quality of evidence is low, especially in terms of long‐term outcomes including the impact on the quality‐of‐life.